2018
DOI: 10.3168/jds.2017-13839
|View full text |Cite
|
Sign up to set email alerts
|

Silage review: Recent advances and future uses of silage additives

Abstract: Additives have been available for enhancing silage preservation for decades. This review covers research studies published since 2000 that have investigated the efficacy of silage additives. The review has been divided into 6 categories of additives: homofermentative lactic acid bacteria (LAB), obligate heterofermentative LAB, combination inoculants containing obligate heterofermentative LAB plus homofermentative LAB, other inoculants, chemicals, and enzymes. The homofermentative LAB rapidly decrease pH and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
654
4
36

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 627 publications
(728 citation statements)
references
References 128 publications
34
654
4
36
Order By: Relevance
“…The fermentation quality of the FA treated silage compared with untreated silage was in both experiments as described in various publications earlier (Muck et al 2017). Formic acid reduced protein degradation and fermentation as evidenced by low ammonia-N values and low lactic acid and acetic acid contents.…”
Section: Silagesmentioning
confidence: 69%
“…The fermentation quality of the FA treated silage compared with untreated silage was in both experiments as described in various publications earlier (Muck et al 2017). Formic acid reduced protein degradation and fermentation as evidenced by low ammonia-N values and low lactic acid and acetic acid contents.…”
Section: Silagesmentioning
confidence: 69%
“…In addition, this process may potentially enhance dry matter intake and ruminal digestibility of alfalfa silages (Sun et al 2009;Khota et al 2016). However, these positive results are not consistent in previous studies assessing cellulase treated alfalfa silages (Kozelov et al 2008;Muck et al 2018), possibly due to the selectivity of cellulases for specific fibre components (high lignin concentration) of certain lucerne materials (Wilson et al 1994). Previous studies have reported that the combined addition of LAB and cellulase may have a synergetic effect on silage quality Ni et al 2014;Tian et al 2014).…”
Section: Introductionmentioning
confidence: 74%
“…When oxygen enters the silo during silage production, or during silage supply to animals, the multiplication of some groups of aerobic or aerobic facultative microorganisms are favoured, especially molds and yeasts, and some proteolytic bacteria that use energy silage 32 , which increases the losses of DM and nutritional value, negatively affecting the productive performance of the animals.…”
Section: Discussionmentioning
confidence: 99%